MHD flow past a parabolic flow past an infinite isothermal vertical plate in the presence of thermal radiation and chemical reaction - Sivakumar, Pushparaj; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
The problem of MHD free convection flow with a parabolic starting motion of an infinite isothermal vertical plate in the presence of thermal radiation and chemical reaction has been examined in detail in this paper. The fluid considered here is a gray, absorbing emitting radiation but a non-scattering medium. The dimensionless governing coupled linear partial differential equations are solved using the Laplace transform technique.
Keywords: MHD; isothermal; radiation; vertical plate; thermal radiation; chemical reaction; Laplace transforms technique